The impacts of macroeconomic indicators towards FBM KLCI / Andy Sukardy Parawangi - Parawangi, Andy Sukardy (2014)
The purpose of this study is to determine the significant relationship between macroeconomic risks and stock price. The macroeconomic variables comprises of interest rate, exchange rate, money supply, GDP and FDI . This project paper used longitudinalhorizon for 30 years period of 1983 until 2012 and used Eviews software to analyze it. The significance of this paper is to help managers of company to understand the factors that may influence the company share price especially macroeconomic variables. The scope of this study is within Malaysia. Furthermore, this study employs proxy to a few of the selected macroeconomic variables such as FBM KLCI for stock index, BLR for interest rate, M2 for money supply and GDP for economic growth. Multiple Linear Regression Model and also Pearson correlation is employed in order to analyze the data.